Internalisasi Goal Congruance untuk Pendeteksian Financial Statement Fraud Berbasis Behaviour Audit (Studi Kasus KAP Benny dan Rekan) - Jamaluddin Majid; Alfian Fani; Marwah Gama (IAIN Manado, 2019)
This research aims to reveal goal congruence for the financial statement fraud- based behavioral audit. financial statement fraud. The agency relationship theory is a contract between the auditor (agent) and the principal (principal). Agency relationships arise when one or more principals employ another person (agent) to provide a service and then delegate authority to decision making to the agent. This study was conducted at KAP Benny and colleagues using qualitative research using phenomenology approach using secondary data and primary data analyzed using interview and interview method using tools in the form of recorder and manuscript aid and tested its validity. The result of this research is shown by case from from 2015 to 2017. In 2015 there was 86.3% of cases, in 2016 there was 86.7% and down in 2017 by 3.68%. Auditors' perception of goal congruence can help in achieving the goal of information that is not synchronized with other information. For that in building a good goal congruence then we need to build the ethics of an auditor.